2020
DOI: 10.2147/ott.s241337
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pulmonary Lymphoepithelioma-Like Carcinoma: A Mini-Review</p>

Abstract: Pulmonary lymphoepithelioma-like carcinoma (PLELC) is a rare and distinct subtype of non-small-cell lung carcinoma associated with Epstein-Barr virus (EBV) infection. We systematically reviewed the recent research that expands our knowledge about PLELC, with main focus on its genetic profile, tumor-infiltrating environment, PD-L1 expression, circulating EBV-DNA, clinical utility of 18F-FDG PET/CT, and treatment strategy. A low frequency of typical driver mutations and widespread existence of copy number variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 81 publications
2
14
0
Order By: Relevance
“…The same scenarios were also observed in Wang et al's study (29) and Chang et al's study (30). The results above indicated that typical driver gene mutations, the main etiology of other common NSCLCs, might not play a critical role in the carcinogenesis of LELC (31). Furthermore, EGFR or ALK-targeted agents might not be suitable in the neoadjuvant or adjuvant therapy of advanced LELC.…”
Section: Discussionsupporting
confidence: 78%
“…The same scenarios were also observed in Wang et al's study (29) and Chang et al's study (30). The results above indicated that typical driver gene mutations, the main etiology of other common NSCLCs, might not play a critical role in the carcinogenesis of LELC (31). Furthermore, EGFR or ALK-targeted agents might not be suitable in the neoadjuvant or adjuvant therapy of advanced LELC.…”
Section: Discussionsupporting
confidence: 78%
“…The same scenarios were also observed in Wang et al's study [30] and Chang et al's study [31]. The results above indicated that typical driver gene mutations, the main etiology of other common NSCLCs, might not play a critical role in the carcinogenesis of LELC [32]. Furthermore, EGFR or ALK-targeted agents might not be suitable in the neoadjuvant or adjuvant therapy of advanced LELC.…”
Section: Discussionsupporting
confidence: 78%
“…However, the oligoprogression of three of the bone metastases was confirmed approximately six months after the start of pembrolizumab maintenance. In addition, the prognostic value of circulating EBV-DNA in pulmonary LELC has been described in [11]. In the current case, the circulating EBV-DNA was not measured.…”
Section: Discussionmentioning
confidence: 71%